2017
DOI: 10.18632/oncotarget.22911
|View full text |Cite
|
Sign up to set email alerts
|

Can urologists introduce the concept of “oligometastasis” for metastatic bladder cancer after total cystectomy?

Abstract: We investigated whether the concept of oligometastasis may be introduced to the clinical management of metastatic bladder cancer patients. Our study population comprised 128 patients diagnosed with metastatic bladder cancer after total cystectomy at our 6 institutions between 2004 and 2014. We extracted independent predictors for identifying a favorable. Occurrence that fulfilled all 4 criteria which were independently associated with cancer-specific death was defined as oligometastasis: a solitary metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…In our study, patients with oligometastasis had better outcomes than those of patients with multiple metastases (83.5% vs 52.5%, P < .001). In many kinds of cancers, oligometastasis is an independent prognostic factor, including NPC . Some studies have shown that after systemic therapy, patients with oligometastasis can reach more than 5 years of progress‐free survival .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients with oligometastasis had better outcomes than those of patients with multiple metastases (83.5% vs 52.5%, P < .001). In many kinds of cancers, oligometastasis is an independent prognostic factor, including NPC . Some studies have shown that after systemic therapy, patients with oligometastasis can reach more than 5 years of progress‐free survival .…”
Section: Discussionmentioning
confidence: 99%
“…Patients from our single‐institution center with oligometastatic urothelial carcinoma from January 2013 to December 2016 were screened. Oligometastatic urothelial carcinoma was defined by three or fewer metastatic lesions and no liver metastases, similarly to the classification proposed by Ogihara et al . Among 41 advanced urothelial patients admitted to our department over the period, we identified seven (17%) patients who underwent SBRT for metastatic node lesions with the aim of either to consolidate the response to a previous systemic treatment or to delay the beginning of systemic chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that metastatic disease with node‐only involvement and good PS has a better prognosis compared with patients with visceral metastasis (bone, lung and liver) and/or poor PS . Furthermore, urothelial carcinoma with oligometastases (defined as a solitary metastatic organ; number of metastatic lesions of ≤3; the largest diameter of metastatic foci of ≤5 cm; no liver metastases) has a favorable prognosis compared with non‐oligometastatic disease …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the bad prognosis of metastatic UC (mUC), a subgroup of patients lives longer than 5 years after diagnosis. This subgroup consists of oligometastatic patients presenting with ≤3 metastatic lesions in a single organ (but no liver), and with the largest diameter of metastatic foci of ≤ 5 cm [66]. The critical question remains the definition of the imaging tool to optimise the finding of oligometastatic disease.…”
Section: Urothelial Bladder Cancermentioning
confidence: 99%